Analisis Kepemimpinan dan Motivasi Kerja terhadap Kinerja Karyawan : Studi Kasus pada PT HATNI - Silvia Dwi Indriana (BADAN PENERBIT STIEPARI PRESS, 2026)
This study examines the influence of leadership style and work motivation on employee performance at PT HATNI. Problems arise due to the low level of coaching and work results. The purpose of this study is to analyze the relationship between these three variabeles ti improve the effectiveness of human resource management at PT HATNI. Using a qualitative approach, this study seeks to understand the realitonship between leadership, work motivation, and employee performance from various perspective, both structural and psychological. The results show that the leadership style at PT HATNI Lamongan is transformational and participatory, with leaders plying an active role in motivation and employee in decisions. Work motivation is influenced by intrinsic factors, but employees still expect improved facilities and a fairer reward system to increase morale and performance. This study shows that leadership and work motivation have a positive effect on employee performance at PT HATNI. Leardership is still predominantly transctional, so it needs to be strengthened to become more inspirational and communicative transformationl. Work motivation is a major factor in improving performance, so a reward system that is fair, transparent, and encrourages sustainable productivity is needed.